The role of 4.0 industry on the digital and ecological transformation of the seaport ecosystem. A case study of the Algerian Port Community System (APCS) - Gharbi Nedjoua; Béatrice Marie Meurier (Journal of North African Economies, 2025)
The objective of this paper is to show how Industry 4.0 may help digital transformation occur by transforming ports from ecosystems to smart, sustainable ports. This paper relies on a study of the Algerian port community system (APCS). The results of the study reveals that very positive outcomes were achieved through the adoption of technologies; for example; reducing the period of passage of goods through the ports by five days. This brings revenues equivalent to 13.15 million dollars per year, and the digitization of 75% of documents along ports supply chain. However, for Algerian ports, the digital transformation and their exposure to bureaucratic obstacles and opposition from government institutions hindered good progress. Have the economic and political will by all the port logistics stakeholders. Also, the building of partnerships with specialized competencies are the keys to the success of the smart and sustainable ports project in Algeria.